2020
DOI: 10.1111/wrr.12826
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide‐rich hydrogel formulation combined with photobiomodulation repairs UV‐induced photodamage in mice skin

Abstract: Prolonged skin exposure to ultraviolet radiation (UVR) induces premature aging in both the epidermis and the dermis. Chronic exposure to UVR induces the activation of mitogen‐activated protein kinase (MAPK) signaling pathway, activating c‐Jun, c‐Fos expression, and transcription factor of AP‐1 activating protein. AP‐1 activation results in the positive induction of matrix metalloproteinase (MMP) synthesis, which degrade skin collagen fibers. Polysaccharides from the fruit of Lycium barbarum (LBP fraction) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Recent studies have reported that c-Fos expression was elevated in a skin photodamage model in mice, 39 which is consistent with our findings. Based on the results of this study, we speculate that although c-Fos expression was increased in the model mice, it did not bind to the CLDN1 promoter due to the low expression of WAKMAR2 (which could not assist c-Fos localization to the CLDN1 promoter).…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have reported that c-Fos expression was elevated in a skin photodamage model in mice, 39 which is consistent with our findings. Based on the results of this study, we speculate that although c-Fos expression was increased in the model mice, it did not bind to the CLDN1 promoter due to the low expression of WAKMAR2 (which could not assist c-Fos localization to the CLDN1 promoter).…”
Section: Discussionsupporting
confidence: 93%
“…43 In an in vivo wound model, photobiomodulation treatment combined with a topical hydrogel prepared from the fruit of Lycium barbarum was shown to decrease MMP-1/-2/-9 expression as well as c-Fos/c-Jun, and increase collagen I/III level, inhibit skin thickening caused by ultraviolet radiation. 44 In the results of our study, we showed that the mRNA expression of c-jun was significantly higher in the tissue of hyperglycemic rats, and it decreased significantly with metformin treatment on the 3rd day compared to the 0th day. In addition, there was a significant decrease in c-jun expression on all three treatment days compared to day 0, while a significant increase was observed in the control groups on the 3rd day.…”
Section: Discussionsupporting
confidence: 48%
“…However, in another study, they showed that high glucose increased the mRNA and protein level of AP1 subunits c‐Fos/c‐Jun, resulting in the activation of AP1 in diabetic skin tissue 43 . In an in vivo wound model, photobiomodulation treatment combined with a topical hydrogel prepared from the fruit of Lycium barbarum was shown to decrease MMP‐1/‐2/‐9 expression as well as c‐Fos/c‐Jun, and increase collagen I/III level, inhibit skin thickening caused by ultraviolet radiation 44 . In the results of our study, we showed that the mRNA expression of c‐jun was significantly higher in the tissue of hyperglycemic rats, and it decreased significantly with metformin treatment on the 3rd day compared to the 0th day.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LBP pretreatment significantly improved the reproductive function of Wistar rats, significantly upregulated the expression of Bcl-2, while downregulating the expression of Bax, and inhibited the apoptosis of spermatogenic cells [84]. Lycium barbarum also promoted cell proliferation and prevented apoptosis by regulating the expression of metalloproteinases [85] and modulating the Nrf2/ARE pathway, and the p38 MAP, MAPK pathway [26,[86][87][88]. It prevented ultra violet (UV)-induced skin and eye damage due to its antioxidant and antiapoptotic effects [27], the inhibition of the mitochondrial pathway, and the phosphorylation of c-Jun NH2-terminal kinase (JNK) [89] (Table 2).…”
Section: Radioprotective Effects and Molecular Mechanisms Of Lycium B...mentioning
confidence: 98%